Strategy for Fulfilling Resources and Managing Education Financing in Primary Schools - Wuryandoko, Santoso; Purwati, Sri; Sugiyarto, Sugiyarto; Nurkolis, Nurkolis (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2024)
One of the important problems in educational development in almost every country in the world is education financing. Education financing is an activity related to obtaining the funds received and how these funds are used to finance all educational programs that have been determined. This research aims to determine the sources of education financing and how elementary school education financing is managed in Blora Regency. The method used in this research is qualitative method. The research was conducted in three elementary schools in Blora Regency. The data collection method in this research was carried out in three ways, namely: interviews, observation, and documentation. The research results are: (1) Fulfillment of funding sources for primary school education in Blora Regency comes from three main sources, namely: central government, regional government, and the community; (2) Management of primary school education financing in Blora Regency has been carried out in three stages, namely: planning education financing, implementing education financing and evaluating education financing.